“Easternization” of Post-Western International Order: Appertaining Confucianism into Bandung Conference Legacy - Dedi Dinarto (Institute of International Studies, 2015)
This paper seeks to develop non-Western theory in IR, particularly appertaining Confucianism into the formation of new global order. Arguably, the role of China in international order has generated debates for IR theorists, which ended in two main conclusions, China as a new hegemonic power or responsible power. It is presumably caused by the diffusion of power in post-Cold War global order, in which China seeks for revival after the ‘century of humiliation’ caused by Western presence in early 20th century. Moreover, the model of China’s leadership under Xi Jinping in which global order is assumed to be related with the revival of Confucianism. Stressing on mutual cooperation, China seeks to shift the international paradigm disorder dominated by the western idea of materialism. Distinctively, this paper will illustrate the notion of Chinese role in the global order by taking its connection with the formation of Bandung Conference. As one of the global leading power, China could play greater role in international sphere, among other by uniting members of developing countries in the Bandung Conference to revivethe alternative way of global order management. Furthermore, the promotion of Chinese Dream as the manifestation of the essence of confucianism under Xi Jinping could become the starting point toward “easternization” of global order under Bandung Conference legacy.